2021
DOI: 10.1007/s11356-021-14480-7
|View full text |Cite
|
Sign up to set email alerts
|

Uncurtaining the effect of COVID-19 in diabetes mellitus: a complex clinical management approach

Abstract: The aim of the present review is to overview the common properties of corona virus and hence proofs well beginning of corona virus in persons with diabetes, and its treatment. Globally, it has been observed that according to the statistics, India has the second largest number of people with diabetes. Literature review has been implemented within the databases using suitable keywords. For persons suffering from diabetic disorder, the COVID-19 infection becomes a dual challenge. Diabetes is a severe metabolic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 96 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Reportedly, 17.14% (18/105) of medical staff were serologically 16), the risk of ESFHCWs' exposure to SARS-CoV-2 could be effectively reduced. One doctor was infected only 1 day after work, which may be related to the fact that he had type II diabetes and did not receive the third dose of a COVID-19 vaccine (17)(18)(19)(20). Also, in our study, we found that the total score of infection prevention and control status of nurses was higher than that of doctors, and the difference was statistically significant, suggesting that the infection prevention and control status of doctors should be improved.…”
Section: Discussionmentioning
confidence: 53%
“…Reportedly, 17.14% (18/105) of medical staff were serologically 16), the risk of ESFHCWs' exposure to SARS-CoV-2 could be effectively reduced. One doctor was infected only 1 day after work, which may be related to the fact that he had type II diabetes and did not receive the third dose of a COVID-19 vaccine (17)(18)(19)(20). Also, in our study, we found that the total score of infection prevention and control status of nurses was higher than that of doctors, and the difference was statistically significant, suggesting that the infection prevention and control status of doctors should be improved.…”
Section: Discussionmentioning
confidence: 53%
“…[25] With an unfavourable support system against this public health threat, diabetic patients having COVID-19 infection should follow normal course of antihypertensive and antidiabetic drugs prescribed with the exception of sodium glucose cotransporter-2 inhibitors which may increase the risk of dehydration and ketoacidosis. [26] A cornerstone of management of type 2 diabetes mellitus includes optimum weight management [27] and regular physical activity. [28] Physically active (PA) people have less severe symptoms, shorter recovery times, and are less likely to infect others, besides developing better immunity after an anticipated vaccination and minimize future complications.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…In December 2019, a series of acute and atypical respiratory diseases was identified in Wuhan, China. The source of the illnesses was attributed to a novel coronavirus, named the SARS-CoV-2, and the subsequent disease it caused was named the COVID-19, and on 11 March 2020 it was declared a pandemic by the WHO 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%